Impact of meteorological parameters on COVID-19 pandemic: A comprehensive study from Saudi Arabia - Mohammad Alkhowailed; Ali Shariq; Fuhaid Alqossayir; Osama A. Alzahrani; Zafar Rasheed; Waleed Al Abdulmonem (Informatics in Medicine Unlocked, 2020)
Background: The Coronavirus disease 2019 (COVID-19) has now been declared a global public health disaster with no currently available vaccine. This study was undertaken to analyse the effect of meteorological parameters such as temperature, humidity, and wind speed on the spread of ongoing COVID-19 in Saudi Arabia. Methods: The COVID-19 dashboard for five major cities of Saudi Arabia - Riyadh, Makah, Jeddah, Medina and Dammam was used for data collection. The data on weather were collected from the Weather Underground Company (IBM business GA, USA, 2020). The data were analysed by Spearman's rank correlations using JASP statistical software in two main sections. In the first section the data on COVID-19 from cities were combined to analyse the overall picture of COVID-19 and in the second section, different meteorological parameters such as temperature, humidity and wind speed were analysed. Results: Novel data revealed interesting facts on the spreading of COVID-19 in Saudi Arabia, the data showed that the number of COVID-19 positive cases increases due to the decrease of temperature or humidity, whereas an average decrease in the wind speed was also found to be associated with an elevation of the number of positive cases. Conclusions: This study determined the impact meteorological factors on the infectivity rate of COVID-19. An inverse association was found between the meteorological parameters with the spreading of COIVD-19. Therefore, this study directs the health authorities to implement specific measures against the spreading of this global pandemic based on weather patterns.